Measuring Underemployment: Establishing the Cut-off Point - Guntur Sugiyarto (Asian Development Bank (ADB), 2007)
Unemployment and underemployment are the most pressing problems in Asia today, which is reflected in the widespread underutilization rate of about 29% of the total labor force. In addition to the fact that most of the labor force in developing countries cannot afford to be completely unemployed, the standard labor force framework currently in use worldwide is biased toward counting labor force as employed rather than as unemployed. This systematically undervalues the full extent of the unemployment problem. This paper suggests a better way to determine the threshold to measure underemployment using the cluster method. The robustness of its results is assessed using ANOVA tests, Chow test, and recursive dynamic regressions. Overall, results indicate that the proposed cut-off point of 40 working hours per week is the best one.
hdl:11540/1850
Keywords: 330